Early childhood education teachers’ conceptions of children’s rights and the role of early education for children’s rights - Ann Quennerstedt (Cogent Education)
The article examines Swedish early childhood education teachers’ conceptions of children’s rights and their understanding of the role and assignment of early childhood education in relation to rights. The study also investigates how understandings have changed over time as teachers were interviewed in two different rounds ten years apart. Four conceptions of what children’s rights entail in early childhood education were identified: children should be respected, children are entitled to feel safe, learning is a right, and rights for children need to be adapted. Each of these centres a specific right or rights aspect, in turn pointing out a particular task for early childhood education. The four right conceptions appear at both interview times; however, a higher proportion of the teachers express them in the second round of interviews, and the reasoning around the notions is more elaborated at this point. The findings consequently indicate a high stability over time in early childhood teachers’ basic understanding of children’s rights and what the role of education is. At the same time, teachers’ awareness and knowledge of children’s rights have evidently increased over time.